Propagation pattern of cracks around a shale borehole via the cohesive element method - Dexu Sun (Journal of Petroleum Exploration and Production Technology)
Abstract Shale gas is a cutting edge energy source for development, and reserves are abundant. However, shale microcracks develop and tend to form macroscopic fractures during drilling, which can cause severe wellbore instability. Therefore, in combination with rock mechanics theory and fracture mechanics theory, the cohesive element method is adopted to establish a numerical model for differential crack propagation due to bottomhole pressure on the basis of the B-K fracture criterion. The propagation pattern of cracks around a wellbore is simulated, and the influences of rock mechanical parameters, the initial crack length, the direction of crack distribution, and minimum horizontal stress on crack propagation are analyzed. The research results indicate that the larger the Young’s modulus of shale is, the easier it is for cracks to propagate. The Poisson’s ratio of shale has a large influence on crack widening, but its effect on the crack length is weak. The larger the angle between the crack and the maximum horizontal stress is, the more difficult it is for the crack to propagate. The greater the minimum horizontal stress is, the more difficult it is for cracks to propagate. The initial crack length has a weak effect on crack propagation.